2014
DOI: 10.1038/eye.2014.221
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging including spectral-domain optical coherence tomography and confocal near-infrared reflectance for characterization of lacquer cracks in highly myopic eyes

Abstract: Purpose To compare multimodal imaging in detecting lacquer cracks in highly myopic eyes, and to correlate these findings with those of spectral-domain optical coherence tomography (SD-OCT). Methods An observational case series study. Patients with a refractive error worse than À 8 diopters and lacquer cracks were recruited. The rates of detection of the lacquer cracks using multimodal imaging including near-infrared reflectance (NIR) imaging, fundus autofluorescence (FAF) imaging, and fluorescence angiography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…ICGA shows linear hypofluorescence at the area of the lacquer cracks, while the appearance of the lacquer cracks is obscured on FA, especially at the early stage of development. Liu et al 26 reported that near-infrared reflectance, which has relatively high sensitivity for detecting lacquer cracks compared with ICGA, FA and autofluorescence, showed the hyper-reflective line; spectral-domain OCT showed a thinner choroid and an acoustic shadow at the area of the lacquer cracks and a continuous RPE-Bruch's membrane line overlaying the lacquer cracks and fundus autofluorescence, which detected only 12.5% of lacquer cracks, showed linear hypoautofluorescence. Consistent with these findings, we hypothesised that lacquer cracks develop as mechanical breaks in Bruch's membrane due to axial elongation, after which RPE atrophy should develop.…”
Section: Discussionmentioning
confidence: 99%
“…ICGA shows linear hypofluorescence at the area of the lacquer cracks, while the appearance of the lacquer cracks is obscured on FA, especially at the early stage of development. Liu et al 26 reported that near-infrared reflectance, which has relatively high sensitivity for detecting lacquer cracks compared with ICGA, FA and autofluorescence, showed the hyper-reflective line; spectral-domain OCT showed a thinner choroid and an acoustic shadow at the area of the lacquer cracks and a continuous RPE-Bruch's membrane line overlaying the lacquer cracks and fundus autofluorescence, which detected only 12.5% of lacquer cracks, showed linear hypoautofluorescence. Consistent with these findings, we hypothesised that lacquer cracks develop as mechanical breaks in Bruch's membrane due to axial elongation, after which RPE atrophy should develop.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen references were retrieved for screening on full text, [77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94] of which four met the criteria for inclusion in the systematic review. 79,80,82,91 The four new references reported four unique studies. These investigated FAF imaging accuracy for detecting: reticular pseudodrusen in AMD (two studies 80,91 ); hydroxychloroquine-induced retinopathy (one study 79 ); and lacquer cracks in highly myopic eyes (one study 82 ).…”
Section: Results Of the Review Updatementioning
confidence: 99%
“…Lacquer cracks are linear breaks of the Bruch's membrane-choriocapillaris complex, which can be found in 4% of subjects with high myopia [12]. The main pathogenetic mechanism is the mechanical stretching of the chorioretinal structures due to scleral elongation [12].…”
Section: Lacquer Cracksmentioning
confidence: 99%
“…Lacquer cracks are linear breaks of the Bruch's membrane-choriocapillaris complex, which can be found in 4% of subjects with high myopia [12]. The main pathogenetic mechanism is the mechanical stretching of the chorioretinal structures due to scleral elongation [12]. However, according to other studies, their formation could be associated with near vessels perforating the sclera causing the expansion of surrounding scleral tissue [13].…”
Section: Lacquer Cracksmentioning
confidence: 99%
See 1 more Smart Citation